BATASAN DALAM ANONIMITAS: KAJIAN PESAN ANONIM AKUN MENFESS TWITTER - Inas Widyanur Atikah (Jurnal Prodi Ilmu Komunikasi, 2023)
As microblog, Twitter is a social media used by a lot of people to share anything. Twitter’s system makes it easier for people to be anonymous. In Twitter, there are some kinds of bot accounts that operate daily. One of them is menfess (mention confess) account. Through a menfess account, users can send anonymous messages that can reach a lot of other users. Menfess accounts also have their rules, so the sender has to follow it in order to send their messages. However, the sender could still get a hurtful response even when they already followed the rules. Anonymity does not seem to make the sender feel safe because they keep being cautious before sending a message. This cautiousness becomes a kind of boundary. There are several types of boundaries that arise in the anonymous interaction of menfess accounts. Boundaries arise based on the rules written from the menfess account and from the mind of the senders themselves.